2012
DOI: 10.1186/1756-0500-5-458
|View full text |Cite
|
Sign up to set email alerts
|

Distance between residence and the dialysis unit does not impact self-perceived outcomes in hemodialysis patients

Abstract: BackgroundPatients have to travel long distances to undergo hemodialysis (HD) in some regions. We aimed to search for an association of the distance between patients’ residence and the dialysis unit with quality of life, depression and coping among end-stage renal disease (ESRD) patients undergoing maintenance HD.MethodsWe studied 161 ESRD patients undergoing HD during April 2009. Quality of life, depression and coping were assessed by the SF-36, the 10-item CES-D and the Jalowiec Coping Scale, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…However, in multiple regression analysis, rural area was not an independent risk factor for depression. Moreover, the influence of the distance to the dialysis center on variables such as quality of life and depression has been recently studied, and distance was not found to have an effect ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in multiple regression analysis, rural area was not an independent risk factor for depression. Moreover, the influence of the distance to the dialysis center on variables such as quality of life and depression has been recently studied, and distance was not found to have an effect ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…End-stage renal disease (ESRD) is an important health problem worldwide ( Santos & Arcanjo, 2012 ; Bayoumi et al, 2013 ). In Iran, specifically the prevalence and incidence rates of ESRD have increased from 49.9 cases per million people in 2000 to 63.8 cases per million people in 2006, an almost 28% increase over a 6 year period ( Pakpour et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a study in Brazil reported that differences between urban and rural residency. 18 The variations between studies could be explained, in part, by the differences in sample size, study settings, follow-up period, and sociodemographic characteristics as well as socio-economic characteristics of study participants.…”
Section: Discussionmentioning
confidence: 99%